(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
The prevalence of diabetic peripheral neuropathy is predicted to increase in future. The persistent hyperglycaemia results in non-enzymatic glycosylation of haemoglobin and results in macrovascular and microvascular complications. Neuropathy is one of the most frequently encountered microvascular complications. It considerably reduces the quality of life, causes disability due to feet ulceration and gait disturbances. Diabetic peripheral neuropathy can be considered as a Dhatu, Upadhathu pradoshaja vatavyadhi. As Vatavyadhi is mentioned as a Maharoga, combined modalities of treatment should be adopted. As microangiopathy is the underlying pathology, here the integrity and function of Rakthavaha srotas is distorted, which results in Avarana of Vata. To remove this Avarana kapha pitha shamana and Rakta prasadana are the best treatment modalities. Drugs having Rasayanaguna has proven beneficial in restoration of neuronal functions.